“He Who Stands on the Ṭutunjayn” and the Return of Ḥusayn: The Bāb and Jināb-i Bahāʾ in the Prose Writings of Tahirih - Ghaemmaghami, Omid 19XX- (Hawwa, 2023)
While many of Tahirih’s poems have been studied and translated by scholars, her surviving prose works in Arabic and Persian – whose size far outweighs the number of her extant poems – have not received much attention. This article is a further attempt to partially fill this noticeable lacuna by exploring Tahirih’s prodigious prose oeuvre. Special attention will be given to a neologism Tahirih invokes to describe the Bāb and to the many references in her later writings to the return of Imam Ḥusayn.